Tonsil‐derived mesenchymal stem cells (T‐MSCs) prevent Th17‐mediated autoimmune response via regulation of the programmed death‐1/programmed death ligand‐1 (PD‐1/PD‐L1) pathway. (12th June 2017) - Kim, Ji‐Yon; Park, Minhwa; Kim, Yu‐Hee; Ryu, Kyung‐Ha; Lee, Kyung Ho; Cho, Kyung‐Ah; Woo, So‐Youn
Abstract: Our knowledge of the immunomodulatory role of mesenchymal stem cells (MSCs) in both the innate and adaptive immune systems has dramatically expanded, providing great promise for treating various autoimmune diseases. However, the contribution of MSCs to Th17‐dominant immune disease, such as psoriasis and its underlying mechanism remains elusive. In this study, we demonstrated that human palatine tonsil‐derived MSCs (T‐MSCs) constitutively express both the membrane‐bound and soluble forms of programmed death‐ligand 1 (PD‐L1), which enables T‐MSCs to be distinguished from MSCs originating from other organs (i.e. bone marrow or adipose tissue). We also found that T‐MSC‐derived PD‐L1 effectively represses Th17 differentiation via both cell‐to‐cell contact and a paracrine effect. Further, T‐MSCs increase programmed death‐1 (PD‐1) expression on T‐cells by secreting IFN‐β, which may enhance engagement with PD‐L1. Finally, transplantation of T‐MSCs into imiquimod‐induced psoriatic skin inflammation in mice significantly abrogated disease symptoms, mainly by blunting the Th17 response in a PD‐L1‐dependent manner. This study suggests that T‐MSCs might be a promising cell source to treat autoimmune diseases such as psoriasis, via its unique immunoregulatory features. Copyright © 2017 John Wiley & Sons, Ltd.